Effects of Obesity and Low and High Isoflavones in Soy Protein Concentrate Diet on Liver Steatosis. (7th June 2021) - Kozaczek, Melisa; Korourian, Soheila; Spary, Beverly; Irby, David; Hakkak, Reza
Abstract: Objectives: To examine the role of isoflavones levels in soy protein diets on protection against Non-Alcoholic Fatty Liver Disease (NAFLD) in obese rat model (8 weeks of feeding). Methods: 42 six-week old lean ( n  = 21) and obese ( n  = 21) Zucker rats were randomly assigned to one of 3 dietary groups: casein diet (C = control), soy protein with low isoflavones (LIF), or soy protein with high isoflavones (HIF) for 8 weeks ( n  = 7 rats/group). Rats were weighed twice weekly. After 8 weeks, all rats were sacrificed and livers taken for histopathological analysis. Results: Obese rats gained significantly more weight ( P  < 0.0001) than lean rats for all three diet groups, with no significant difference between obese (O) LIF vs. OHIF groups ( P  = 0.19). Body weight was higher in OHIF (717 g) than in OLIF and OC (694 and 620, respectively). No significant difference between LC, LLIF and LHIF ( P between 0.3 and 0.6) was found. Liver steatosis scores were significantly higher in obese rats compared to lean rats ( P  < 0.001). In addition, differences in the steatosis scores between OC vs. OHIF ( P  < 0.0001) were more significant than differences between OC vs. OLIF ( P  = 0.01), and OLIF vs. OHIF ( P  = 0.01) groups, showing the protective effect against liver steatosis exerted by soy protein concentrate with higher isoflavones. Conclusions: We found that soy protein concentrate protects against liver steatosis and protection is more significant with higher concentration of isoflavones. Funding Sources: USDA.